ANALISIS STATUS KEBERLANJUTAN PENGELOLAAN WISATA PANTAI GUCI BATU KAPAL DI DESA MAJA, KALIANDA, LAMPUNG SELATAN - Yuwana Utami Cendrakasih; Indra Gumay Yudha; Darma Yuliana; Henni W Maharani (Jurusan Akuakultur, Universitas Bangka Belitung, 2021)
Tourism is an activity that supported with all the facilities at once the tourist activities which gained benefits parties included tourism or visitors, society and local government. Tourism as one of a development sector and driving force of the wheels of economy could not be released the connection with the sustainable development that had been planned by the government. The sustainable tourism development namely a development that could be supported as ecologically, economy worthy, also fair in ethics and social to society. The purpose of this research was to: (1) analyzing the status of tourist sustainability of Guci Batu Kapal beach from five sustainable dimensions (ecology, economy, technology infrastructure, also law and institutional); (2) Identifying factors that influencing sustainable index of Guci Batu Kapal beach tourism. This research was held on February 2021, in Guci Batu Kapal beach, Maja village, Kalianda, South Lampung. The methods that were used for this research was qualitative methods by descriptive research. Analyzing data that used was analyzing multi-dimensional scaling (MDS) with rapfish approach and leverage analysis. The result of this research showed that tourism of Guci Batu Kapal beach had an index score as 21,58 on a sustainable scale 0-100, which mean include in the bad impact (unsustainable) because of the index score was between in index score of 0-25,00. This analysis of Monte-Carlo showed that the index score of tourism Guci Batu Kapal beach sustainability was not that much different with the Rap-beachtour analysis, the difference obtained only for 0,0001-0,00003. The result was quite stable also the mistake in the input could not be avoided.